The guilds of Ottoman Jerusalem - Cohen, Amnon, 1936- (Ottoman Empire and its heritage, 2001)
This reconstruction of the guilds that functioned in Jerusalem during the Ottoman period draws on the archives of the local court of Muslim Jerusalem, but also includes information on the Jewish and Christan communities. About 50 different guilds are described.